Maxim Violation in the Movie Doctor Strange in the Multiverse of Madness - Nalita Mareta; Ida Zuraida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study is aimed to investigate the violations of maxims cooperative principle uttered in conversations of Doctor Strange in the Multiverse of Madness movie and its intended meaning. This study is designed into a descriptive qualitative research. The data of this study consists of twenty conversations reflecting violation of uttered maxims cooperative principle found in the movie. The data collection is done by observation in several steps such as identifying and marking maxim violation in conversation, classifying each data with Grice’s maxim cooperative principle theory, and giving code on data. Data analysis is done by describing the context of each conversation, then analyzing data by Grice’s maxim cooperative principle. The result shows that 9 data or 45% is categorized into violation of quantity maxim, 6 data or 30% is categorized into violation of quality maxim, 3 data or 15% is categorized into violation of relation maxim, and 2 data or 10% is categorized into violation of manner maxim. From the result, it can be seen that quantity maxim is most often violated in the conversation at whole. Then, the intended meaning of maxim violation is to ignore the conflict, deny the opinion, pressure someone, entertain someone, and change a topic of conversation.